2015
DOI: 10.17951/h.2015.49.3.49
|View full text |Cite
|
Sign up to set email alerts
|

International Marketing under Geopolitical Confrontation

Abstract: Marketing międzynarodowy w warunkach geopolitycznej konfrontacjiKeywords: international marketing, international economic sanctions, international trade disputes, social and cultural contradictions, economic identity, conlict identiication, trade war.Słowa kluczowe: marketing międzynarodowy, międzynarodowe sankcje ekonomiczne, międzynaro-dowe spory handlowe, sprzeczności społeczne i kulturowe, osobowość ekonomiczna, wojna handlowa. JEL Code: F130, M140, D810 IntroductionThe contemporary active internationaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…N. Grazhevska and V. Virchenko analyzed the integration of the traditional labor market into the information and network environment as an essential prerequisite for the transformation of consumer relations [12]. The issue of meeting globalized consumer needs in conditions of political tension is investigated by O. Kanishchenko [17]. A. Starostina, M. Sitncki and other researchers concluded that the dynamics of business environment factors is becoming less predictable and this complicates the analysis of new trends and models of consumer behavior [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…N. Grazhevska and V. Virchenko analyzed the integration of the traditional labor market into the information and network environment as an essential prerequisite for the transformation of consumer relations [12]. The issue of meeting globalized consumer needs in conditions of political tension is investigated by O. Kanishchenko [17]. A. Starostina, M. Sitncki and other researchers concluded that the dynamics of business environment factors is becoming less predictable and this complicates the analysis of new trends and models of consumer behavior [32].…”
Section: Literature Reviewmentioning
confidence: 99%